2022
DOI: 10.7759/cureus.22920
|View full text |Cite
|
Sign up to set email alerts
|

Abducens Nerve Palsy as a Complication of Herpes Zoster Ophthalmicus: A Case Report

Abstract: Herpes zoster (shingles) is a common viral infection that results from the reactivation of varicella-zoster virus (VZV), which remains dormant in sensory ganglia after initial infection. The usual presentation is radicular pain followed by eruption of vesicular rash. herpes zoster ophthalmicus (HZO) is defined as the involvement of ophthalmic division (V1) of the trigeminal nerve (V).Extraocular muscle paralysis is a rare complication of HZO. Here, we report a case of HZO that developed abducens nerve (VI) pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The prognosis of ophthalmoplegia is generally favorable. It was reported that the duration of diplopia associated with ocular motor palsy was between 2 and 23 months [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of ophthalmoplegia is generally favorable. It was reported that the duration of diplopia associated with ocular motor palsy was between 2 and 23 months [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of herpes zoster or shingles, it is important to note that this viral infection can lead to secondary bacterial infections. Herpes zoster is caused by the reactivation of the varicella-zoster virus (VZV) after a period of latency following primary infection with varicella (chickenpox) [ 13 ]. The reactivated virus travels from the dorsal root ganglion down the sensory nerves to the skin, causing a characteristic rash and associated symptoms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%